Attention deficit and hyperactivity and its relationship with learning difficulties among university students - Alsaied, Mohamad Abdullah (Edelweiss Applied Science and Technology, 2024)
Attention deficit combined with hyperactivity is considered one of the most significant challenges faced by children and adolescents in the educational environment. This condition is characterized by three main symptoms: difficulty in concentration, excessive movement, and impulsivity. These symptoms directly impact the student's ability to learn and comprehend, leading to multiple learning difficulties. Difficulty in concentration makes it challenging for the student to follow lessons, pay attention to details, and complete school tasks. The student may easily forget instructions or lose necessary items for assignments and activities. Excessive movement is manifested in the inability to sit quietly, constant fidgeting, and wandering around the classroom without a clear reason. This behavior can distract others and hinder the collective learning process. Impulsivity is evident in acting without thinking, interrupting others, and having difficulty waiting for one's turn. The student may talk excessively or answer questions before they are fully posed. These behaviors negatively affect relationships with teachers and peers, leading to social and psychological challenges. The relationship between attention deficit, hyperactivity, and learning difficulties is strong and interconnected. Students experiencing these symptoms are more susceptible to issues such as dyslexia, dysgraphia, and dyscalculia. These difficulties exacerbate the challenges faced by the student, potentially leading to decreased self-confidence and feelings of frustration. Early intervention and accurate diagnosis play a crucial role in assisting these students. This includes collaboration between parents, teachers, and specialists to develop individualized educational plans that cater to the student's needs. Effective educational strategies include providing a supportive learning environment, using multi-sensory teaching methods, and offering clear and specific instructions. Psychological support and behavioral therapy may be necessary to enhance self-regulation skills and social adaptation. Additionally, community awareness and education about this condition help reduce the social stigma associated with it, enabling students to receive the necessary support. Through joint efforts and understanding, students suffering from attention deficit and hyperactivity can be empowered to achieve their academic and personal potential, overcoming the challenges they face in their educational journey.